Are hybrid vehicles worth it?. - Lave, L.B.
In this paper, the author describes how, despite superior fuel economy and low emissions, hybrid electric vehicles (HEVs) cost too much at present to make economic sense
Keywords: Batteries; Combustion engines; Cost; Economic viability; Fuel cells; Fuel economy; Hybrid electric vehicles; Low emissions